2016
DOI: 10.1002/mnfr.201600387
|View full text |Cite
|
Sign up to set email alerts
|

Impact of red meat consumption on the metabolome of rats

Abstract: This study is the first to identify specific differences in the metabolome related to the intake of red and white meat. These differences may reflect perturbations in endogenous metabolism that can be linked to the proposed harmful effects associated with intake of red meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…It is worth noting that such connection does not necessarily require the presence of oxidation products (that are naturally present in most food systems), as the sustained intake of considerable amounts of unsaturated lipids or animal proteins (both sensitive to oxidation) has been found to increase oxidation and inflammation markers in blood of humans and experimental animals. To exemplify, Jakobsen et al (2017), Turner et al (2017), and Van Hecke et al…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that such connection does not necessarily require the presence of oxidation products (that are naturally present in most food systems), as the sustained intake of considerable amounts of unsaturated lipids or animal proteins (both sensitive to oxidation) has been found to increase oxidation and inflammation markers in blood of humans and experimental animals. To exemplify, Jakobsen et al (2017), Turner et al (2017), and Van Hecke et al…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
“…The interconnection between all these terms is illustrated in Figure 1. Disappointingly, Kanner et al (2017) identify such a diet as a "meal rich in lipids" though it is certainly known that proteinrich foods, such as lean red meat causes postprandial oxidative stress, inflammation, and increased risk to suffer serious diseases, as aforementioned (Jakobsen et al, 2017;Turner et al, 2017). It is assumed that oxidizing lipids play a major role in the pathogenesis of oxidative-driven pathologies while proteins are considered mere recipients of posttranslational changes.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Using high resolution LC‐MS metabolomics, thousands of small molecule metabolites can be detected in a single analysis of a biological sample, such as urine or blood. In addition to host‐derived physiological metabolites, the resulting metabolomic profile includes compounds derived from the diet, which can serve as biomarkers of specific dietary components . Identification of these metabolites allows for better assessment of compliance in dietary interventions, as well as more robust biomarkers of diet quality .…”
Section: Introductionmentioning
confidence: 99%
“…Koeth et al (2013) found that circulating TMAO levels were higher for subjects consuming meat than vegetarians and that TMAO accelerated atherosclerosis in mice [11]. An association between meat intake and TMAO has also been indicated in later studies targeted at discovering biomarkers related to red meat intake [13][14][15]. However, other dietary factors, such as fish consumption, also affect plasma TMAO levels [16].…”
Section: Introductionmentioning
confidence: 99%